Lifetime Trauma Exposure, Gender and DSM-V PTSD Symptoms among Adolescents in Malaysia - Siti Raudzah, Ghazali; Ask, Elklit; Mohamed Ameenudeen, Sultan; Yoke, Y.C (American Psychological Association, 2016)
Abstract Adolescents who have multiple traumatic experiences may suffer from Post-traumatic Stress Disorder (PTSD) or other mental health problems later in life. Study of trauma exposure and PTSD among adolescents is very limited in Malaysia. This study explored the prevalence of lifetime trauma, demographic risk factors, and PTSD symptoms among Malaysian adolescents. This cross-sectional study recruited 1016 adolescents aged 13 to 17 (Mage= 14.9 years). Results showed that 83% participants had at least one traumatic exposure (TE), while prevalence of PTSD symptoms was 10.2%. Adolescents with multiple TEs and those with violent and self-inflicted TE were at significantly higher risk to develop PTSD symptoms. Findings suggest that a large proportion of Malaysian adolescents are exposed to a variety of traumatic events since childhood. Trauma exposure should be included as an important component in our adolescent mental health assessment, allowing early psychological intervention to be provided to those affected. Key words: PTSD, adolescents, gender, lifetime trauma, prevalence, Malaysia